May brings new policies and new people to the UK's parliaments. (4th June 2021) - Ryan, Mandy
Abstract : Mandy Ryan, BVA's head of media and public affairs, outlines how BVA has engaged with and responded to the Queen's Speech and recent parliamentary elections in Scotland and Wales.